Negotiation and compromise in online learning during the Covid-19 pandemic - Nur Endah Januarti; Heru Nugroho; Arie Sujito (Informasi, 2023)
The Covid-19 pandemic has accelerated technological transformation in education. Online learning has become a new culture in education that brings significant changes in the intersubjective relationship between educational actors, which was originally full of warmth but has now turned into formality due to distance meetings. This research aims to reveal the ways of relationship that occur between teachers and students and their consequences in online learning practices. The study used a phenomenological approach by collecting data through interviews with 11 teachers and 11 students and observing the online learning process conducted through various applications. The results of the study showed a weakening of the intersubjective relationship between teachers and students. Distance meetings have turned into mere formalities and emptiness. The closeness and warmth between teachers and students are diminishing and filled with emptiness. The interactions that exist are filled with deceit and fraud. In online learning, teachers and students negotiate and compromise on the learning to be conducted amidst all the limitations of distance learning. The consequence is widespread pragmatism towards technology, with students feeling lonely and isolated, and academic dishonesty increasing. In the end, there is a restriction of relationships and a tendency to prioritize mechanisms of silence as a compromise for the loss of true reality in the teacher-student relationship.